A dual-element-doped calcium fluoride laser transparent ceramic and a preparation method thereof

CN119059818BActive Publication Date: 2026-10-20SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310631462.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2026-10-20
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

激光晶体同样存在系列需要亟需解决的问题,包括(1)激光晶体生长科学和技术的基础问题不清楚;(2)晶体中离子的发光特性、能量传递及其与晶格相互作用的机理缺乏研究;(3)LD抽运高功率密度下(104W/cm2~107W/cm2)激光晶体的热效应及对激光性能的影响等

Benefits of technology

本发明的双元素掺杂氟化钙激光透明陶瓷,其中均为纯氟化钙相,掺杂铒离子后没有形成杂相,Er3+完全固溶进入氟化钙晶格中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004258568930000011
    Figure HDA0004258568930000011
Patent Text Reader

Abstract

The application provides a double-element doped calcium fluoride laser transparent ceramic and a preparation method thereof. The double-element doped calcium fluoride laser transparent ceramic is a manganese-erbium doped calcium fluoride laser transparent ceramic, and the double-element doped calcium fluoride laser transparent ceramic has a light transmittance greater than 90% in the range of 200-1700 nm. In the double-element doped calcium fluoride laser transparent ceramic, both are pure calcium fluoride phases, and no impurity phase is formed after doping erbium ions, and the erbium ions are completely solid-solved into the calcium fluoride crystal lattices. 3+ The double-element doped calcium fluoride laser transparent ceramic has a good ceramic densification degree, and the densification degree is greater than 99%, which is beneficial to improving the optical properties of the ceramic. The light transmittance is greater than 90%, and the performance is excellent. The application further provides a preparation method of the double-element doped calcium fluoride laser transparent ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of laser medium material technology, specifically relating to a dual-element doped calcium fluoride laser transparent ceramic and its preparation method. Background Technology

[0002] Calcium fluoride crystal is an excellent matrix material for laser media. CaF2 has a cubic crystal structure. 2+ Located at the vertices and face centers of the unit cell, occupying F - Half of the cubic void formed, F - Occupied Ca 2+ The entirety of the tetrahedral voids formed by the stacking allows for high-concentration doping of rare-earth ions due to the diversity of their lattice symmetry. It also features a large band gap (-12 eV), a wide transmission range (125 nm to 10 μm), a low refractive index (~1.434, Vis to NIR), and low phonon energy (~390 cm⁻¹). -1 Rare earth-doped calcium fluoride materials exhibit different forms of charge compensation, which easily leads to the formation of broad and smooth absorption and emission spectra, thus facilitating the generation of ultrashort pulsed lasers.

[0003] Solid-state laser materials include laser glass and laser crystals. Among them, laser glass is a solid-state laser material with glass as the matrix, which is widely used in various types of solid-state laser devices and has become the main laser material for high-power and high-energy lasers. Laser glass consists of two parts: matrix glass and activating ions. The various physical and chemical properties of laser glass are mainly determined by the matrix glass, while its spectral properties are mainly determined by the activating ions. As the matrix glass of laser glass, optical glass is currently the most commonly used. Laser glass must have various suitable spectral properties, good transparency and good physical and chemical properties. It is difficult to manufacture laser glass that meets the above requirements at the same time. There are currently four main development directions for laser crystals: violet-blue-green and visible light laser crystals; mid-infrared laser crystals; (1μm band) high-power, high-energy laser crystals; LD-pumped ultrafast laser gain and amplification crystals. Laser crystals also have a series of problems that need to be solved urgently, including (1) the basic problems of laser crystal growth science and technology are unclear; (2) the luminescence characteristics, energy transfer and interaction mechanism of ions in the crystal with the lattice are lacking research; (3) the high power density of LD pump (10 4 W / cm 2 ~10 7 W / cm 2 The thermal effects of laser crystals and their impact on laser performance, etc.

[0004] Therefore, a new laser medium matrix material still needs to be developed. Summary of the Invention

[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides a dual-element doped calcium fluoride laser-transparent ceramic, which has good densification, which is beneficial to improving the optical properties of the ceramic, with a light transmittance greater than 90% and excellent performance.

[0006] The present invention also provides a method for preparing a dual-element doped calcium fluoride laser transparent ceramic.

[0007] The first aspect of the present invention provides a dual-element doped calcium fluoride laser transparent ceramic, wherein the dual-element doped calcium fluoride laser transparent ceramic is a manganese-erbium doped calcium fluoride laser transparent ceramic, and the transmittance of the dual-element doped calcium fluoride laser transparent ceramic is greater than 90%.

[0008] One of the technical solutions of the present invention concerning dual-element doped calcium fluoride laser-transparent ceramics has at least the following beneficial effects: The present invention comprises a dual-element doped calcium fluoride laser-transparent ceramic, wherein all phases are pure calcium fluoride phases, and no impurity phases are formed after erbium ion doping. 3+ It completely dissolves into the calcium fluoride lattice.

[0009] The dual-element doped calcium fluoride laser-transparent ceramic of this invention has a high degree of ceramic densification, which is beneficial to improving the optical properties of the ceramic. It has a light transmittance greater than 90% and exhibits excellent performance.

[0010] According to some embodiments of the present invention, the density of the dual-element doped calcium fluoride laser transparent ceramic is greater than 99%.

[0011] A second aspect of the present invention provides a method for preparing the aforementioned dual-element doped calcium fluoride laser-transparent ceramic, comprising the following steps: S1: Prepare preparations containing F respectively - Anionic solutions and solutions containing Mn 2+ Er 3+ and Ca 2+ A cationic solution; S2: Add the anion solution to the cation solution, mix well, let stand and age, centrifuge, wash and dry the precipitate to obtain powder; S3: Sinter the powder to obtain the dual-element doped calcium fluoride laser transparent ceramic.

[0012] One technical solution of the present invention relating to the preparation method of dual-element doped calcium fluoride laser transparent ceramics has at least the following beneficial effects: Currently, the main methods for preparing fluoride transparent ceramics are single-crystal hot forging and hot pressing sintering of chemically synthesized powders. Single-crystal hot forging is limited by the drawbacks of single-crystal growth, while the laser output effect of transparent ceramics obtained by hot pressing sintering of chemically synthesized powders is not ideal. This invention presents a method for preparing dual-element doped calcium fluoride laser transparent ceramics, in which Er... 3+ The powder is completely dissolved into the calcium fluoride lattice, and the particle size is moderate, which facilitates the removal of pores during the later sintering process. The resulting ceramic has a good degree of densification, which is beneficial to improving the optical properties of the ceramic.

[0013] The present invention discloses a method for preparing dual-element doped calcium fluoride laser-transparent ceramics, in the synthesis of (Mn) 2+ +Er 3+ During the chemical reaction of CaF2 powder, Mn 2+ and Er 3+ It enters the lattice structure of CaF2 and follows Mn 2+ and Er 3+ As the doping concentration increases, the number of lattice defects in the powder increases, resulting in lower crystallinity. For the sintering process, defects in the powder crystals are beneficial to improving sintering activity and can significantly improve its sintering performance. Therefore, in the preparation method of the dual-element doped calcium fluoride laser transparent ceramic of this invention, no sintering aids are required, the raw materials are readily available, and the preparation method is simple.

[0014] The present invention provides a method for preparing dual-element doped calcium fluoride laser transparent ceramics that does not require expensive equipment or complex process control, has undemanding reaction conditions, and is easy to industrialize, thus broadening the application range of laser medium matrix materials.

[0015] According to some embodiments of the present invention, in the anionic solution, F - The concentration ranges from 0.5 mol / L to 2.5 mol / L.

[0016] According to some embodiments of the present invention, the solvent in the anionic solution includes water.

[0017] According to some embodiments of the present invention, the fluorine source in the anionic solution includes KF·2H2O.

[0018] According to some embodiments of the present invention, in the cation solution, Mn 2+ Er 3+ and Ca 2+ The concentrations were all between 0.5 mol / L and 2.5 mol / L.

[0019] According to some embodiments of the present invention, the solvent in the cation solution includes water.

[0020] According to some embodiments of the present invention, the manganese source in the cation solution includes Mn(NO3)2·4H2O.

[0021] According to some embodiments of the present invention, the erbium source in the cation solution includes Er(NO3)3·5H2O.

[0022] According to some embodiments of the present invention, the calcium source in the cation solution includes Ca(NO3)2·4H2O.

[0023] According to some embodiments of the present invention, in the cation solution, Mn 2+ Er 3+ and Ca 2+ The molar ratio is (1~5):(3~10):(96~85).

[0024] When Mn 2+ and Er 3+ Excessive content can lead to some Mn 2+ and Er 3+ Mn failed to dissolve into the CaF2 crystal lattice and existed as fluorides. After sintering, these fluorides accumulated at the grain boundaries, affecting the transmittance of the sintered body. Therefore, Mn 2+ Er 3+ and Ca 2+ The molar ratio of (1~5):(3~10):(96~85) is a suitable range.

[0025] Mn during powder synthesis 2+ and Er 3+ Within the CaF2 crystal structure, as the doping concentration increases, the particle size of the powder decreases, and the powder tends to become cubic. In this invention, Mn is specified... 2+ Er 3+ and Ca 2+ The molar ratio ensures that Mn 2+ and Er 3+ It completely dissolves into the CaF2 lattice without affecting the subsequent sintering performance of the ceramic.

[0026] According to some embodiments of the present invention, during the process of adding the anion solution to the cation solution, the addition rate of the anion solution is 1 mL / min to 2.5 mL / min.

[0027] According to some embodiments of the present invention, during the process of adding the anion solution to the cation solution, the anion solution is added by titration.

[0028] According to some embodiments of the present invention, the particle size of the powder gradually decreases with increasing titration rate. When the titration rate is too fast, the powder particles nucleate too quickly, resulting in insufficient powder growth time. Simultaneously, powder agglomeration affects subsequent sintering activity. Therefore, a titration rate of 1 mL / min to 2.5 mL / min is suitable.

[0029] According to some embodiments of the present invention, the process of adding the anion solution to the cation solution is accompanied by stirring.

[0030] According to some embodiments of the present invention, the stirring speed is 200 rpm to 300 rpm.

[0031] According to some embodiments of the present invention, the anion solution is added to the cation solution, and after the addition is complete, the mixture is stirred for 20 to 40 minutes and then allowed to stand for aging.

[0032] According to some embodiments of the present invention, the settling and aging time is 10h to 15h.

[0033] As the aging time increases, the powder changes from disordered polygons to cubic structures. Excessive aging time can lead to excessively large powder particles, which is not conducive to the elimination of pores during sintering. Therefore, 10 to 15 hours is the appropriate standing aging time.

[0034] According to some embodiments of the present invention, the centrifugation speed is 3500 rpm to 4000 rpm.

[0035] According to some embodiments of the present invention, the centrifugation time is 2 min to 3 min.

[0036] According to some embodiments of the present invention, the precipitate is washed with deionized water and ultrasonically treated.

[0037] According to some embodiments of the present invention, the number of cleaning cycles can be 3 to 5.

[0038] According to some embodiments of the present invention, the powder is dried after cleaning.

[0039] According to some embodiments of the present invention, the washed precipitate can be placed in a blower-type constant temperature oven at about 60°C and dried for 20 hours. After drying, it can be passed through a 100-mesh sieve, and the sieved powder can be placed in an oven at 120°C and dried for later use.

[0040] According to some embodiments of the present invention, the sintering temperature is 650℃~750℃; and / or, the sintering time is 2h~3h; and / or, the sintering heating rate is 1℃ / min~1.5℃ / min.

[0041] The temperature was increased to 650℃~750℃ at a rate of 1℃ / min~1.5℃ / min and held for 2~3 hours. At this sintering temperature, the grain size increased rapidly, and pores were gradually eliminated with increasing sintering temperature, resulting in near-complete densification of the ceramic. The heating rate of 1℃ / min~1.5℃ / min allowed sufficient time for pores to be eliminated during the low-temperature sintering stage, and also sufficient time for the internal and external temperatures of the sample to remain consistent, thus synchronizing the densification process.

[0042] According to some embodiments of the present invention, the method further includes, after step S3, coarse grinding and polishing of the dual-element doped calcium fluoride laser transparent ceramic.

[0043] According to some embodiments of the present invention, coarse grinding can be performed on sandpaper.

[0044] According to some embodiments of the present invention, the polishing process can be performed on a polishing machine. Attached Figure Description

[0045] Figure 1 This is an X-ray powder diffraction pattern of the dual-element doped calcium fluoride laser transparent ceramic prepared in Example 1. Detailed Implementation

[0046] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0047] In some embodiments of the present invention, the present invention provides a dual-element doped calcium fluoride laser transparent ceramic, wherein the dual-element doped calcium fluoride laser transparent ceramic is a manganese-erbium doped calcium fluoride laser transparent ceramic, and the density of the dual-element doped calcium fluoride laser transparent ceramic is greater than 99% and the light transmittance is greater than 90%.

[0048] It should be noted that the dual-element doped calcium fluoride laser transparent ceramic of the present invention consists entirely of pure calcium fluoride phase, and no impurity phase is formed after doping with erbium ions. 3+ It completely dissolves into the calcium fluoride lattice.

[0049] It is understood that the dual-element doped calcium fluoride laser transparent ceramic of the present invention has a high degree of ceramic densification, which is beneficial to improving the optical properties of the ceramic. It has a light transmittance greater than 90% and excellent performance.

[0050] It is understood that the dual-element doped calcium fluoride laser transparent ceramic of the present invention has a good degree of ceramic densification, with a density greater than 99%.

[0051] In other embodiments of the present invention, a method for preparing the dual-element doped calcium fluoride laser-transparent ceramic of the present invention is provided, comprising the following steps: S1: Prepare preparations containing F respectively- Anionic solutions and solutions containing Mn 2+ Er 3+ and Ca 2+ A cationic solution; S2: Add the anion solution to the cation solution, mix well, let stand and age, centrifuge, wash and dry the precipitate to obtain powder; S3: Sintered powder, which yields dual-element doped calcium fluoride laser transparent ceramic.

[0052] Understandably, current methods for preparing transparent fluoride ceramics mainly involve single-crystal hot forging and hot pressing sintering of chemically synthesized powders. Single-crystal hot forging is limited by the drawbacks of single-crystal growth, while the laser output effect of transparent ceramics obtained by hot pressing sintering of chemically synthesized powders is not ideal. This invention presents a method for preparing dual-element doped calcium fluoride laser-transparent ceramics, in which Er... 3+ The powder is completely dissolved into the calcium fluoride lattice, and the particle size is moderate, which facilitates the removal of pores during the later sintering process. The resulting ceramic has a good degree of densification, which is beneficial to improving the optical properties of the ceramic.

[0053] It can also be understood that the preparation method of the dual-element doped calcium fluoride laser transparent ceramic of the present invention involves the synthesis of (Mn) 2+ +Er 3+ During the chemical reaction of CaF2 powder, Mn 2+ and Er 3+ It enters the lattice structure of CaF2 and follows Mn 2+ and Er 3+ As the doping concentration increases, the number of lattice defects in the powder increases, resulting in lower crystallinity. For the sintering process, defects in the powder crystals are beneficial to improving sintering activity and can significantly improve its sintering performance. Therefore, in the preparation method of the dual-element doped calcium fluoride laser transparent ceramic of this invention, no sintering aids are required, the raw materials are readily available, and the preparation method is simple.

[0054] Furthermore, the preparation method of the dual-element doped calcium fluoride laser transparent ceramic of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, and it is easy to realize industrial production, thus broadening the application range of laser medium matrix materials.

[0055] In some embodiments of the present invention, in the anionic solution, F - The concentration ranges from 0.5 mol / L to 2.5 mol / L.

[0056] In some embodiments of the present invention, the solvent in the anionic solution includes water.

[0057] In some embodiments of the present invention, the fluorine source in the anionic solution includes KF·2H2O.

[0058] In some embodiments of the present invention, in the cation solution, Mn 2+ Er 3+ and Ca 2+ The concentrations were all between 0.5 mol / L and 2.5 mol / L.

[0059] In some embodiments of the present invention, the solvent in the cationic solution includes water.

[0060] In some embodiments of the present invention, the manganese source in the cation solution includes Mn(NO3)2·4H2O.

[0061] In some embodiments of the present invention, the erbium source in the cation solution includes Er(NO3)3·5H2O.

[0062] In some embodiments of the present invention, the calcium source in the cation solution includes Ca(NO3)2·4H2O.

[0063] In some embodiments of the present invention, in the cation solution, Mn 2+ Er 3+ and Ca 2+ The molar ratio is (1~5):(3~10):(96~85).

[0064] When Mn 2+ and Er 3+ Excessive content can lead to some Mn 2+ and Er 3+ Mn failed to dissolve into the CaF2 crystal lattice and existed as fluorides. After sintering, these fluorides accumulated at the grain boundaries, affecting the transmittance of the sintered body. Therefore, Mn 2+ Er 3+ and Ca 2+ The molar ratio of (1~5):(3~10):(96~85) is a suitable range.

[0065] Mn during powder synthesis 2+ and Er 3+ Within the CaF2 crystal structure, as the doping concentration increases, the particle size of the powder decreases, and the powder tends to become cubic. In this invention, Mn is specified... 2+ Er 3+ and Ca 2+ The molar ratio ensures that Mn 2+ and Er 3+ It completely dissolves into the CaF2 lattice without affecting the subsequent sintering performance of the ceramic.

[0066] In some embodiments of the present invention, during the process of adding the anion solution to the cation solution, the addition rate of the anion solution is 1 mL / min to 2.5 mL / min.

[0067] In some embodiments of the present invention, the anion solution is added to the cation solution by titration.

[0068] In some embodiments of the present invention, the particle size of the powder gradually decreases with increasing titration rate. When the titration rate is too fast, the powder particles nucleate too quickly, resulting in insufficient powder growth time. Simultaneously, powder agglomeration affects subsequent sintering activity. Therefore, a titration rate of 1 mL / min to 2.5 mL / min is suitable.

[0069] In some embodiments of the present invention, the process of adding the anionic solution to the cation solution is accompanied by stirring.

[0070] In some embodiments of the present invention, the stirring speed is 200 rpm to 300 rpm.

[0071] In some embodiments of the present invention, an anion solution is added to a cation solution, and after the addition is complete, the mixture is stirred for 20 to 40 minutes and then allowed to stand for aging.

[0072] In some embodiments of the present invention, the aging time is 10h to 15h.

[0073] As the aging time increases, the powder changes from disordered polygons to cubic structures. Excessive aging time can lead to excessively large powder particles, which is not conducive to the elimination of pores during sintering. Therefore, 10 to 15 hours is the appropriate standing aging time.

[0074] In some embodiments of the present invention, the centrifugation speed is 3500 rpm to 4000 rpm.

[0075] In some embodiments of the present invention, the centrifugation time is 2 min to 3 min.

[0076] In some embodiments of the present invention, the precipitate is washed with deionized water and ultrasonically treated.

[0077] In some embodiments of the present invention, the cleaning may be performed 3 to 5 times.

[0078] In some embodiments of the present invention, the powder is dried after cleaning.

[0079] In some embodiments of the present invention, the washed precipitate can be placed in a blower-type constant temperature oven at about 60°C for 20 hours to dry. After drying, it can be passed through a 100-mesh sieve, and the sieved powder can be placed in an oven at 120°C to dry for later use.

[0080] In some embodiments of the present invention, the sintering temperature is 650°C to 750°C; and / or the sintering time is 2h to 3h; and / or the sintering heating rate is 1°C / min to 1.5°C / min.

[0081] The temperature was increased to 650℃~750℃ at a rate of 1℃ / min~1.5℃ / min and held for 2~3 hours. At this sintering temperature, the grain size increased rapidly, and pores were gradually eliminated with increasing sintering temperature, resulting in near-complete densification of the ceramic. The heating rate of 1℃ / min~1.5℃ / min allowed sufficient time for pores to be eliminated during the low-temperature sintering stage, and also sufficient time for the internal and external temperatures of the sample to remain consistent, thus synchronizing the densification process.

[0082] In some embodiments of the present invention, the method further includes, after step S3, coarse grinding and polishing of the dual-element doped calcium fluoride laser transparent ceramic.

[0083] In some embodiments of the invention, coarse grinding can be performed on sandpaper.

[0084] In some embodiments of the present invention, the polishing process can be performed on a polishing machine.

[0085] The technical solution of the present invention will be better understood below with reference to specific embodiments.

[0086] Example 1 This embodiment provides a dual-element doped calcium fluoride laser-transparent ceramic, specifically a manganese-erbium doped calcium fluoride laser-transparent ceramic. The specific preparation method is as follows: (1) Dissolve 0.001 mol of Mn(NO3)2·4H2O, 0.003 mol of Er(NO3)3·5H2O and 0.096 mol of Ca(NO3)2·4H2O in 100 mL of deionized water to prepare a cation solution, and dissolve 0.3 mol of KF·2H2O in 200 mL of deionized water to prepare an anion solution; (2) Add the anion solution to the cation solution at a rate of 1 mL / min and stir until homogeneous. The stirring rate is 200 rpm. After titration, continue stirring for 40 min and then let stand for 10 h to age. (3) After aging, the solution is centrifuged at 3500 rpm for 3 min, the lower layer precipitate is taken out, washed with deionized water and ultrasonically treated. After repeated centrifugation, washing and ultrasonic treatment three times, the precipitate is placed in a 60℃ forced-air constant temperature oven to dry for 20 h. After drying, it is passed through a 100-mesh sieve, and the sieved powder is placed in a 120℃ oven to dry for later use. (4) Place the powder into a graphite mold, place the graphite mold in a vacuum hot press furnace for high-temperature sintering, raise the temperature to 700°C at a rate of 1°C / min, and hold for 2 hours to obtain manganese erbium doped calcium fluoride laser transparent ceramic.

[0087] Figure 1 This is the X-ray powder diffraction pattern of the dual-element doped calcium fluoride laser-transparent ceramic prepared in this embodiment, for reference. Figure 1 As can be seen, compared with the standard spectrum of calcium fluoride, the XRD peak positions of the transparent ceramic obtained in this embodiment have not changed significantly, and all peaks are pure calcium fluoride phase with no other impurity peaks appearing, indicating that no impurity phase was formed after doping with erbium ions.

[0088] The ceramic obtained in this embodiment has a density greater than 99%, and after double-sided polishing with a grinding and polishing machine, its light transmittance is greater than 92% in the range of 200~1700nm.

[0089] Example 2 This embodiment provides a dual-element doped calcium fluoride laser-transparent ceramic, specifically a manganese-erbium doped calcium fluoride laser-transparent ceramic. The specific preparation method is as follows: (1) Dissolve 0.005 mol of Mn(NO3)2·4H2O, 0.01 mol of Er(NO3)3·5H2O and 0.085 mol of Ca(NO3)2·4H2O in 100 mL of deionized water to prepare a cation solution, and dissolve 0.4 mol of KF·2H2O in 200 mL of deionized water to prepare an anion solution; (2) Add the anion solution to the cation solution at a rate of 2.5 mL / min and stir until homogeneous. The stirring rate is 250 rpm. After titration, continue stirring for 30 min and then let stand for 13 h to age. (3) After aging, the solution is centrifuged at 4000 rpm for 2 min, the lower layer of precipitate is taken out, washed with deionized water and ultrasonically treated. After repeated centrifugation, washing and ultrasonic treatment three times, the precipitate is placed in a 60℃ forced-air constant temperature oven to dry for 20 h. After drying, it is passed through a 100-mesh sieve, and the sieved powder is placed in a 120℃ oven to dry for later use. (4) Place the powder into a graphite mold, place the graphite mold in a vacuum hot press furnace for high-temperature sintering, raise the temperature to 750°C at a rate of 1.5°C / min, and hold for 2 hours to obtain manganese erbium doped calcium fluoride laser transparent ceramic.

[0090] The ceramic obtained in this embodiment has a density greater than 99%, and after double-sided polishing with a grinding and polishing machine, its light transmittance is greater than 90% in the range of 200~1700nm.

[0091] Example 3 This embodiment provides a dual-element doped calcium fluoride laser-transparent ceramic, specifically a manganese-erbium doped calcium fluoride laser-transparent ceramic. The specific preparation method is as follows: (1) Dissolve 0.004 mol of Mn(NO3)2·4H2O, 0.006 mol of Er(NO3)3·5H2O and 0.09 mol of Ca(NO3)2·4H2O in 100 mL of deionized water to prepare a cation solution, and dissolve 0.5 mol of KF·2H2O in 200 mL of deionized water to prepare an anion solution; (2) Add the anion solution to the cation solution at a rate of 2 mL / min and stir until homogeneous. The stirring rate is 300 rpm. After titration, continue stirring for 20 min and then let stand for 15 h to age. (3) After aging, the solution is centrifuged at 4000 rpm for 2.5 min, the lower precipitate is taken out, washed with deionized water and ultrasonically treated. After repeated centrifugation, washing and ultrasonic treatment three times, the precipitate is placed in a 60℃ forced-air constant temperature oven to dry for 20 h. After drying, it is passed through a 100-mesh sieve, and the sieved powder is placed in a 120℃ oven to dry for later use. (4) Place the powder into a graphite mold, place the graphite mold in a vacuum hot press furnace for high-temperature sintering, raise the temperature to 750°C at a rate of 1.5°C / min, and hold for 3 hours to obtain manganese erbium doped calcium fluoride laser transparent ceramic.

[0092] The ceramic obtained in this embodiment has a density greater than 99.5%, and after double-sided polishing with a grinding and polishing machine, its light transmittance is greater than 93% in the range of 200~1700nm.

[0093] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A dual-element doped calcium fluoride laser-transparent ceramic, characterized in that, The dual-element doped calcium fluoride laser transparent ceramic is a manganese-erbium doped calcium fluoride laser transparent ceramic. The transmittance of the dual-element doped calcium fluoride laser transparent ceramic is greater than 90% in the range of 200~1700nm, and the density of the dual-element doped calcium fluoride laser transparent ceramic is greater than 99%.

2. A method for preparing the dual-element doped calcium fluoride laser-transparent ceramic as described in claim 1, characterized in that, Includes the following steps: S1: Prepare preparations containing F respectively - Anionic solutions and solutions containing Mn 2+ Er 3+ and Ca 2+ A cationic solution; S2: Add the anion solution to the cation solution, mix well, let stand and age, centrifuge, wash and dry the precipitate to obtain powder; S3: Sinter the powder to obtain the dual-element doped calcium fluoride laser transparent ceramic.

3. The method according to claim 2, characterized in that, In the anion solution, F - The concentration ranges from 0.5 mol / L to 2.5 mol / L.

4. The method according to claim 2, characterized in that, In the cation solution, Mn 2+ Er 3+ and Ca 2+ The concentrations were all between 0.5 mol / L and 2.5 mol / L.

5. The method according to claim 4, characterized in that, In the cation solution, Mn 2+ Er 3+ and Ca 2+ The molar ratio is (1~5):(3~10):(96~85).

6. The method according to claim 2, characterized in that, During the process of adding the anion solution to the cation solution, the addition rate of the anion solution is 1 mL / min to 2.5 mL / min.

7. The method according to claim 2, characterized in that, The settling and aging time is 10h~15h.

8. The method according to claim 2, characterized in that, The sintering temperature is 650℃~750℃; and / or the sintering time is 2h~3h; and / or the sintering heating rate is 1℃ / min~1.5℃ / min.

9. The method according to claim 2, characterized in that, The method further includes, after step S3, coarse grinding and polishing of the ceramic.